Asuhan Akupunktur Pada Pasien Hipertensi di Klinik Sinshe AI SIN TCM Yogyakarta - Kuryati Kuryati; Amal Prihatono; Ikhwan Abdullah; Puspo Wardoyo (Universitas Malahayati Lampung, 2026)
ABSTRACT Hypertension is a condition characterized by an abnormal and persistent increase in blood pressure observed across multiple measurements, caused by one or more risk factors that fail to function properly in maintaining normal blood pressure. Acupuncture can reduce blood pressure by stimulating acupuncture points to facilitate and regulate the flow of Qi in the body, thereby restoring Yin–Yang balance. This single-case study aimed to determine the benefits of acupuncture care for a patient with hypertension at Sinshe Ai Sin TCM Clinic, Yogyakarta. The study was conducted as a single-case design over six therapy sessions involving one male participant aged 50 years who had been experiencing hypertension for the past six months. Data collection techniques included observation (Wang), interview (Wen), listening and smelling (Wen), and palpation (Qie), in accordance with the standards of Traditional Chinese Medicine. The selection of acupuncture points was based on the syndrome of Liver Yang Hyperactivity, with therapeutic principles focused on calming the Liver, suppressing excessive Liver Yang, and clearing heat. The therapeutic evaluation results demonstrated gradual and consistent improvement. The participant’s blood pressure decreased from 170/100 mmHg during the first therapy session to 130/80 mmHg by the sixth session. Complaints of headache and abdominal bloating resolved, sleep quality improved, and emotional stability was enhanced. Keywords: Hypertension, Acupuncture Therapy, Liver Yang Hyperactivity. ABSTRAK Hipertensi adalah suatu keadaan dimana terjadi peningkatan tekanan darah secara abnormal dan terus menerus pada beberapa kali pemeriksaan tekanan darah yang disebabkan satu atau beberapa faktor risiko yang tidak berjalan sebagaimana mestinya dalam mempertahankan tekanan darah secara normal. Akupunktur dapat menurunkan tekanan darah dengan cara merangsang titik akupunktur untuk menghantarkan serta melancarkan Qi tubuh dalam upaya menyeimbangkan Yin Yang. Penelitian studi kasus ini bertujuan untuk mengetahui manfaat Asuhan Aupunktur pada pasien Hipertensi di Klinik Sinshe Ai Sin TCM Yogyakarta. Penelitian dilakukan dalam bentuk studi kasus tunggal selama enam sesi terapi pada satu orang partisipan laki-laki berusia 50 tahun yang mengalami Hipertensi sejak 6 bulan yang lalu. Teknik pengumpulan data meliputi observasi (Wang), wawancara (Wen), pendengaran dan penciuman (Wen), dan perabaan (Qie) sesuai standar ilmu pengobatan Tiongkok. Pemilihan titik akupunktur didasarkan pada sindrom Hiperaktivitas Yang Hati dengan prinsip terapi yang diterapkan adalah Menenangkan Hati, menekan Yang Hati yang berlebih, dan membersihkan panas. Hasil evaluasi terapi menunjukkan adanya perbaikan yang bertahap dan konsisten. Tekanan darah partisipan mengalami penurunan dari 170/100 mmHg pada terapi pertama menjadi 130/80 mmHg pada terapi ke-6. Keluhan sakit kepala dan perut kembung menghilang, kualitas tidur membaik, serta kondisi emosional menjadi lebih stabil. Kata Kunci: Hipertensi, Terapi Akupunktur, Hiperaktivitas Yang Hati.